Studi Pengelasan TIG pada Material SUS 304 Ditinjau dari Kekuatan dan Sifat Mekanis : TIG Welding Study on SUS 304 Material in Terms of Strength and Mechanical Properties - Saleh, Mochamad (Civiliza Publishing, Indonesia., 2023)
TIG (Tungsten Inert Gas) welding is a metal joining method widely used in industry because it is capable of producing smooth, clean, and high-precision welds. However, in austenitic stainless steel SUS 304, the welding process often causes changes in mechanical properties due to thermal cycling that affect tensile strength, hardness, and toughness. This study aims to analyze the effect of TIG welding on the strength and mechanical properties of SUS 304 and to identify optimal parameters that can maintain the material's structural integrity. The method used is a qualitative approach with direct observation of the welding process, in-depth interviews with practitioners, and documentation of the results of tensile, hardness, and toughness tests in the laboratory, which were carried out for three months in the workshop and material laboratory. The results show that TIG joints in SUS 304 have tensile strength close to that of the parent material, the hardness distribution varies between zones, and the toughness decreases especially under high heat input conditions. The analysis of the results also confirms that welding parameter control plays an important role in preventing grain growth and sensitization phenomena that reduce mechanical properties. In conclusion, this study provides theoretical contributions to strengthen the study of the relationship between welding parameters and the mechanical properties of SUS 304, as well as practical contributions in the form of guidance for industry in optimizing joint quality.